Design of Long-Distance Shrimp Pond Monitoring Using 2.4 GHz IoT Digital Radio Line-of-Sight Transmission - Hamdani, Fadil; Fitriawan , Helmy; Septiana, Trisya; Heriansyah (Faculty of Engineering, Universitas Lampung Jl. Soemantri Brojonegoro No.1 Bandar Lampung, Indonesia 35141, 2025)
Water quality plays a vital role in shrimp farming, as suboptimal conditions can increase stress levels and disease susceptibility, potentially resulting in mass mortality. Real-time water quality monitoring enabled by Internet of Things (IoT) technology presents a promising solution to this issue. However, implementing IoT systems in shrimp ponds, typically situated in open, low-vegetation, and aquatic environments, poses technical challenges, particularly in maintaining line-of-sight (LOS) conditions between sensor nodes and gateway nodes. This study utilizes a linear path profiling method to evaluate LOS feasibility. A straight-line path is drawn between the transmitter and receiver to determine the minimum required antenna height for unobstructed signal propagation. For a 2.4 GHz WiFi-based transmission over a 1.27 km distance, ensuring 30% Fresnel zone clearance requires the sensor antenna to be elevated 1.5 meters above the water surface, while the gateway antenna must be positioned at a minimum height of 6.5 meters above ground level, assuming a ground elevation of 1.5 meters above mean sea level (AMSL). To achieve a minimum Received Signal Level (RSL) of -80 dBm, simulation results indicate that the system needs a transmit power of at least 12 dBm when using a gateway antenna with 8 dBi gain, or 8 dBm if the gateway antenna has 20 dBi gain, assuming the transmitter antenna gain is 2 dBi. The study also presents a simulation-based relationship between RSL and transmit power across different receiver antenna gains (2 dBi, 8 dBi, and 20 dBi), providing insights for optimizing IoT-based monitoring systems in aquaculture environments.